Toll-like receptor (TLR) expression on CD4+ and CD8+ T-cells in patients chronically infected with hepatitis C virus - Hammond, T.; Lee, S.; Watson, M.; Flexman, J.; Cheng, W.; Fernandez, S.; Price, Patricia (2010)
Toll-like receptor (TLR) expression on T-cells and the signalling pathways that lead to the production of cytokines may limit antigen-specific T-cell responses. Here, expression of TLR and retinoic acid inducible gene I (RIG-I) on T-cells were evaluated in patients chronically infected with hepatitis C virus (HCV), before and during pegylated interferon-a and ribavirin therapy. Expression of TLR2,3,4,7,9 and retinoic acid inducible gene (RIG)-I on different CD4+ and CD8+ T-cell sub-populations (naïve: CD45RA+CD57-; central memory: TCM CD45RA-CD57-; effector memory: TEM CD45RA-CD57+ and terminally differentiated effector memory: TEMRA CD45RA+CD57+) were measured by flow cytometry. TLR7, TLR9 and RIG-I expression on CD4+ T-cells and RIG-I expression on CD8+ T-cells was higher in patients than healthy controls. Therapy increased expression of TLR2, TLR4 and TLR9 and this was observed for all T-cell sub-populations. Evaluation of TLR expression at baseline did not identify patients able to achieve sustained virological response following therapy. © 2010.